Problematizing Modern Democracy in the United States: - Julia Simon (Politische Vierteljahresschrift, 2023)
Since Donald Trump's presidency and the diverse efforts to undermine the transfer of power after the 2020 election, the risks of extreme polarization and democratic backsliding in the United States (US) have been highlighted in the literature. Yet the epistemic dimension of these developments remains underresearched. Embedded in a~genealogical Foucauldian governmentality/counter-conduct approach, this contribution addresses the puzzle of how election denialism and related (violent) anti-system activity are being rationalized, legitimized, and anchored in political subjectivities as efforts to 'protect' American democracy. This perspective allows to inquire into liberalism's authoritarian potential that can be mobilized through different forms of counter-conduct. The study analytically disentangles these forms based on their prime targets, modes of operation, and the forms of knowledge they rely on. Focusing on the swing state of Arizona, the empirical analysis furthermore highlights the role of the subnational level in interlinking counter-conduct and (autocratizing) governmental practices in a~federal system. Conceptually, the study renders visible a~profound struggle over the epistemic foundations of the current liberal constitutional and political order that clearly transcends the issue of the 2020 election, Donald Trump, and even the context of the United States. Indeed, similar patterns of subjectivation and counter-conduct can also be detected for example in Germany. Moreover, this paper expands the scope of the concept of counter-conduct to study radical right-wing contestations and related questions of epistemic (in)justice. It thereby seeks to encourage debate on how political science can address the pluralization and polarization of contents, standards, and forms of knowledge as they become relevant to democratic backsliding.
Keywords: 320; Democratic backsliding; Governmentality/counter-conduct; Radical right; Conspiracism; Polarization; Subjectivity; Radikale Rechte; Verschwörungstheorien; Polarisierung; Subjektivitäten